Ответы и объяснения

2013-11-25T17:39:23+00:00
9x^6*y^5
--------------=1,5x^2y^2
y^3*6x^4
x*(x+2)^2     x(x+2)
--------------=  ----------
(x+2)*2          2
3(a-3)*(a-2)(a+2)       3(a-2)
----------------------- = -----------
(a+2)(a-3)(a+3)         (a+3)

#2
(x+y)^2-(x-y)^2    x^2-y^2         x^2+2xy+y^2-x^2+2xy-y^2         4xy
------------------- : ------------- =  --------------------------------------- = ------- = 4
x^2-y^2                   xy                             xy                                xy